Leksička kontrastivna analiza i rječnici - Fuchs, Milena Žic (Array, 1986)
Summary: Lexical contrastive studies are a neglected part of contrastive analysis in general. Since little attention has been payed to the possible basis for lexical contrastive analysis, conceptual dictionaries (in combination with bilingual dictionaries and existing corpora) are suggested as a possible starting point. This kind of approach would ensure a more detailed insight into the structure of the vocabulary, as well as lexical gaps and ways of lexicalization of each language.